PREDIKSI KELULUSAN MAHASISWA TEPAT WAKTU BERDASARKAN USIA, JENIS KELAMIN, DAN INDEKS PRESTASI MENGGUNAKAN ALGORITMA DECISION TREE - Agus Romadhona; Suprapedi Suprapedi; Heribertus Himawan (Jurnal Teknologi Informasi - Cyberku (JTIC), 2017)
Prediction of the study period in college is needed in determine the accuracy of the students study period according to the specified time so that wisdom of prevention related to the study period is no ton time could be done. This research aims to find patterns to predict the timely graduation of students usingdata mining techniques and models to predict long period of study was Decision tree algorithm C4.5 to compare with ID3 and CHAID algorithms using test data to determine the percentage of precision, recall and accuracy is obtained that the algorithm Decision Tree C4.5 has a better performance compared with other algorithms. From this research it was found that the prediction of the students study period are affected by incoming students age, gender, GPA semesters 1 through 4 semesters GPA and the most influential is the 4th semester GPA of students graduate on time with a value of 0.340 gain of all attributes. Decision tree algorithm C4.5 reaches the highest accuracy on the amount of data 389 with 91.51% accuracy values for k-fold=3, 90.75 for k-fold = 5 and 90.77 with k-fold = 10, While ID3 and CHAID algorithms achieving a low accuracy value. So thus the value accuracy of Decision Tree algorithm C4.5 is better than the ID3 and CHAID algorithm. In this research, training data are used as much as 389. To see better performance in the accuracy of the results of each algorithm, thus for furthermore research the number of data records used training process should be improved.